Effects of NAO on the climatic water budget at the Polish southern Baltic coast - Świątek, Małgorzata (Bulletin of Geography. Physical Geography Series, 2016)
Abstract: Effects of the North Atlantic Oscillation (NAO) on the Standardized Precipitation-Evaporation Index (SPEI), a metric of the climate-dependent water budget, in the Polish part of the southern Baltic coastal areas were analysed. The analyses were based on monthly NAO index values calculated by P.D. Jones, T. Jonsson, and D. Wheeler for 1951-2010 and on monthly temperatures and sums of precipitation in Szczecin, Ustka, and Elbląg used to calculate SPEI. No strong effects of NAO on the water budget could be demonstrated. Intensified air mass advection from the west was found to slightly reduce SPEI in the Polish coastal zone. In winter (particularly in February), the reduction was caused by the temperature increase during air mass advection from the west, which increases evaporation. In summer (mainly in August), the effect was due to the decreased sum of precipitation, the reduction, however, not being significant. Therefore, NAO effects on the water budget are considered weak and irregular.